New technique for the treatment of fresh bony mallet finger: A retrospective case series study - Yue, Zhenshuang; Mo, Yafeng; Xiong, Zhenfei; Tang, Yanghua (Frontiers in Surgery, 2023)
Background: The bony mallet finger is a tear fracture of the extensor tendon, resulting in a flexion deformity of the finger, which affects both the function of the finger. The classical Ishiguro’s method is associated with damage to the cartilage of the distal interphalangeal (DIP) joint and always lead to the joint stiffness. This paper explores a new technique to overcome the shortcomings of the classical Ishiguro’s method and achieve better clinical efficacy. Methods: We examined 15 patients with bony mallet fingers, 9 males and 6 females, from February 2020 to June 2022, ranged from 23 to 58 years, including 1 case of index finger, 5 cases of middle finger, 3 cases of ring finger and 6 cases of little finger. The median course of the injury to surgery was 2 days (range, 1~7 days). All had fresh closed injuries, according to the Wehbe and Schneider classification: 4 cases of type IA, 6 cases of type IB, 3 cases of type IIA and 2 cases of type IIB. All patients were treated surgically by the new technique. Post-operative follow-up was conducted to record the healing of the fracture, the pain of the affected finger and the function of joint movement. Results: The 15 cases were followed up after surgery. The median active range of motion was 65° (range, 55~75°). The median extension deficit of DIP joint was 0° (range, 0~11°). The median clinical healing time of the fracture was 6 weeks (range, 6~10 weeks). None of the patients experienced significant pain. The patients were assessed according to the Crawford criteria at the final follow-up: 11 cases were assessed as excellent, 3 cases were assessed as good and 1 case was assessed as fair. No loss of fracture repositioning, loosening of internal fixation, skin necrosis or infection was observed. Conclusion: The application of the new technique for the treatment of bony mallet fingers has the advantages of good stability, fracture healing and functional recovery of the DIP joint, making it an ideal surgical procedure for the treatment of fresh bony mallet fingers.